Politik Kebijakan Kolonial dalam Program Perumahan Rakyat di Medan, 1909-1942 - Sitepu, Desy Hariyanti (Local History & Heritage, 2024)
This article discusses the city government's policy in addressing settlement problems in colonial-era Medan. This research uses the historical method, by conducting a series of source searches from archives, contemporaneous newspapers, reports, and literature studies. The findings of this research are first, the city government created a public housing policy (volkhuisvesting) that started in 1918. This policy aimed to fulfill the housing needs of the urban poor. However, in practice the number built was insufficient and the rent set was not affordable by the community. Secondly, the city government evicted hundreds of houses that were considered dilapidated in the villages in Medan. The two policies implemented by the government simultaneously aimed to support each other as a political colonial policy in controlling urban and village spaces in Medan.